2006
DOI: 10.1016/j.fm.2006.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Moulds and yeasts in fruit salads and fruit juices

Abstract: Thirty-eight fruit salad samples including cantaloupe, citrus fruits, honeydew, pineapple, cut strawberries and mixed fruit salads, and 65 pasteurized fruit juice samples (apple, carrot, grapefruit, grape and orange juices, apple cider, and soy milk) were purchased from local supermarkets in the Washington, DC area and tested for fungal contamination. The majority of fruit salad samples (97%) were contaminated with yeasts at levels ranging from o2.0 to 9.72 log 10 of colony forming units per gram (cfu/g). Freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
133
1
8

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(151 citation statements)
references
References 14 publications
9
133
1
8
Order By: Relevance
“…limited knowledge of the hazard mycotoxin on fresh produce In the scientific literature some studies indicate the potential presence of mycotoxin producing fungi on fruits, fruit salads and vegetables (Tournas & Katsoudas, 2005;Tournas, Heeres, & Burgess, 2006;Ostry, 2008).…”
Section: Rapid Alert Systems Such As the Rapid Alert Systems For Foodmentioning
confidence: 99%
“…limited knowledge of the hazard mycotoxin on fresh produce In the scientific literature some studies indicate the potential presence of mycotoxin producing fungi on fruits, fruit salads and vegetables (Tournas & Katsoudas, 2005;Tournas, Heeres, & Burgess, 2006;Ostry, 2008).…”
Section: Rapid Alert Systems Such As the Rapid Alert Systems For Foodmentioning
confidence: 99%
“…Existem relatos desse gênero como contaminante de alimentos, apresentando espécies produtoras de micotoxinas (SCHOLLENBERGER et al, 2005;KATSOUDAS, 2005;HEERS;BURGESS, 2006). Foi verificada também a presença da espécie de fungo Cladosporium cladosporioides (Fresen.)…”
Section: Identificação De Fungos Contaminantesunclassified
“…The highest number of yeast colonies was found in grapefruit juice, followed by orange juice, mixed fruit, lemon juice, and fi nally apple juice. Tournas et al (8) found the highest number of yeasts in orange juice and the lowest in the apple juice. Table 2 shows the frequency of isolated yeast species per fruit juice.…”
Section: Methodsmentioning
confidence: 95%